Etoposide phosphate for pediatric orthopedic malignancies after intravenous etoposide hypersensitivity. (January 2020) - Brooks, Joel P; Azmy, Veronica; Thompson, Alison; Luon, Darren; Prozora, Stephanie D; Price, Christina; Hsu, F Ida
Background: Hypersensitivity reactions to etoposide have been reported and patients have been safely transitioned to etoposide phosphate for continued therapy. However, the safety and efficacy of substituting etoposide phosphate for etoposide has not been well established in pediatric orthopedic malignancies. The aim of this study is to determine whether etoposide phosphate can be substituted for etoposide in pediatric orthopedic malignancies. Methods: A chart review of pediatric patients who developed hypersensitivity reactions to etoposide while being treated for orthopedic malignancies was performed at a large academic medical center. Three patients were identified, two with Ewing sarcoma and one with an osteosarcoma. All three patients experienced hypersensitivity reactions to their first doses of etoposide and were switched to etoposide phosphate for further therapy. Results: After premedication, all three patients tolerated full doses of etoposide phosphate without a graded dose challenge or desensitization. Two of the patients were premedicated with diphenhydramine alone, while the third received diphenhydramine and dexamethasone. Conclusions: Etoposide phosphate is a potentially safe alternative for pediatric patients with orthopedic malignancies who experience etoposide hypersensitivity. However, caution is needed as there are cases of etoposide phosphate hypersensitivity.